The continuum of spatially based crises in Latin America. Approach to Venezuelan Geography - Costa, Everaldo Batista da (2023)
This editorial from vol. 6, no. 12 of PatryTer – Latin American and Caribbean Journal of Geography and Humanities recovers the debate that we have developed in different investigations focused on Latin America. This issue also pays tribute to the academic career of geographer Delfina Trinca Fighera, from the University of Los Andes, Mérida, Venezuela.